Pengaruh Perspektif dan Preferensi Pelanggan terhadap Strategi Bauran Pemasaran yang Berorientasi Pelanggan: Studi pada PT Bank Pembangunan Daerah Bali - Anak Agung Putu Agung (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The population of this research was the customers of PT Bank BPD Bali, who reside in various areas across Bali. The sample of the population was selected using judgmental sampling, in which the customers were grouped into individual customers and institution customers (province and regency administrations, LPD, Non-profit Organizations, Corporates) at the bank’s principal branch offices and branch offices all over Bali. The number of the samples, 175 respondents, had met the requirement for maximum probability estimation. Struktural Equation Model Estimation was carried out through full-model analysis to find out about the model’s suitability and the established causal relation in the tested model. The test confirmed the first hypothesis, which stated that the customers’ perspective exerts a significant influence on the design of the marketing strategy. The test also validate the second hypothesis, which stated that the customers’ preferences have a significant influence on the design of the marketing strategy. The third hypothesis, which stated that the design of the marketing strategy has a beneficial influence upon the marketing mix strategy, had also been corroborated with the test. The results of the test supported the theory presented by David W. Cravens dan Nigel F. Piercy (2003) on the marketing strategy process. The theory espoused that the activities to adopt the customers’ perspectives and preferences, in order to find out about their wants and needs, and the activities to devise a marketing strategy design, and the activities to implement the marketing mix strategy, should be treated as integrated activities because the three of them were one unified and comprehensive marketing strategy. The results of this research are expected to provide the management of this Bank with a source of inspiration to be more pro-active in managing customeroriented marketing strategies. It can be achieved by conducting a more integrated marketing activities based on a marketing strategy process. This marketing strategy should also be developed in BPD all across Indonesia as a strategic response to create a sustainable competitive edge in the increasingly competitive world of today’s banking sector.Keywords: customers’ perspectives, customers’ preferences, marketing strategy.